Experimental data processing with a small sample: a combination of probabilistic and interval analysis methods - Potanina, T. V.; Yefimov, O. V. (Одеський національний технологічний університет, 2023)
The applications of the interval and standard probabilistic approaches for verifying the reliability of the results of an experiment studying the mechanical properties of nuclear materials are compared.
Keywords: nuclear materials; mechanical properties; interval probabilistic approaches; standard probabilistic approaches